2021
DOI: 10.1111/jfbc.13826
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different thawing methods on the physicochemical changes, water migration and protein characteristic of frozen pompano ( Trachinotus ovatus )

Abstract: The effects of five thawing methods (ultrasonic thawing [UT], radiofrequency thawing [RFT], water immersion thawing [WIT], microwave thawing [MT], and cold storage thawing [CST]) on physicochemical properties, water migration, and protein characteristic of whole frozen pompano (Trachinotus ovatus) were investigated and compared with fresh samples (FS). The physicochemical changes of thawed pompano were analyzed based on pH, total volatile basic nitrogen (TVB‐N), color difference. The protein aggregation, physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 47 publications
3
12
0
Order By: Relevance
“…The thawing times of CT for the RF and SF groups were 264 min and 451 min, respectively, while the thawing times of WT for those groups were 4.41 min and 8.17 min, respectively ( Figure 1 D), indicating that WT greatly shortened the thawing time of the frozen crayfish. Similar results were also found in the thawing process for the frozen bighead carp ( Aristichthys nobilis ) fillets [ 24 ], as well as the frozen pompano ( Trachinotus ovatus ) [ 25 ]. This might be explained by the fact that the water [0.604 W/(m•K)] has a higher thermal conductivity (i.e., heat transfer rate) than air [0.066 W/(m•K)] [ 19 , 21 ].…”
Section: Resultssupporting
confidence: 70%
“…The thawing times of CT for the RF and SF groups were 264 min and 451 min, respectively, while the thawing times of WT for those groups were 4.41 min and 8.17 min, respectively ( Figure 1 D), indicating that WT greatly shortened the thawing time of the frozen crayfish. Similar results were also found in the thawing process for the frozen bighead carp ( Aristichthys nobilis ) fillets [ 24 ], as well as the frozen pompano ( Trachinotus ovatus ) [ 25 ]. This might be explained by the fact that the water [0.604 W/(m•K)] has a higher thermal conductivity (i.e., heat transfer rate) than air [0.066 W/(m•K)] [ 19 , 21 ].…”
Section: Resultssupporting
confidence: 70%
“…In addition, they found that under constant voltage conditions (10.5 kV), the rate of change of the TVB-N value was inversely proportional to the electrode distance. A similar conclusion was drawn from the other studies regarding electric field-based thawing (Gan et al, 2021;He et al, 2016;Hu et al, 2021;Jia, Sha, et al, 2019;Lan et al, 2021;Mousakhani-Ganjeh et al, 2016b;Qian et al, 2019). Indeed, in addition to HVEFT, other thawing techniques can also achieve lower TVB-N values.…”
Section: Tvb-nsupporting
confidence: 84%
“…Recently, pH, as an essential evaluation index, has frequently appeared in research on various thawing technologies. Lan et al (2021) compared the effects of five thawing methods (UT, 20 • C, 200 W, 33 min; RFT, 25 • C, 27.12 MHz, 22 min; MT, 500 W, 5.8 min; WIT, 16 • C, 40 min and cold storage thawing, CST, 4 • C, 20.6 h) on the physicochemical properties of whole frozen pompano (Trachinotus ovatus) and used pH as an important indicator to evaluate the freshness of the thawed samples. The results showed that pH values of samples treated by RFT and UT were closer to those of the fresh samples (FS) than those of samples treated with the other three methods, while the CST treatment, which had a longer time consumption, resulted in a more noticeable pH increase compared to the fresh samples (pH values of 6.56, 6.54, 6.67, 6.68, 6.55, and 6.80 for FS, UT, RFT, WIT, MT, and CST, respectively).…”
Section: 8mentioning
confidence: 99%
See 1 more Smart Citation
“…The pH of lamb stored for 7 days in the UT group was higher than that in the FW group ( P < 0.05). This was due to the longer thawing time in the FW group, and the loss of minerals with the aqueous solution disrupted the ionic balance in the meat and resulted in a decrease in pH [26] . The pH increase due to storage time may be related to the formation of alkaline compounds in the meat [27] .…”
Section: Resultsmentioning
confidence: 99%